Non-noble metal fuel cell catalysts, methods of making and using the same
Patent Information
- Application Number
- CN202210982979.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-16
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-08-16
AI Technical Summary
[0004]为了解决现有技术存在的上述不足,本发明的目的是提供一种非贵金属燃料电池催化剂及其制备方法和应用,以解决现有燃料电池用非贵金属催化剂中制备工艺复杂,反应条件难以控制,不适合工业化生产的问题
[0009]The beneficial effects of this invention are as follows: Non-precious metals are adsorbed onto the surface and/or interior of anion exchange resin. After adsorption is complete, the substrate is centrifuged and dried to form a precursor supported on the non-precious metal. This adsorption process allows for control of the adsorption amount of non-precious metals, thereby controlling the loading of active components in the catalyst, while also ensuring uniform distribution of the non-precious metals on the support. The precursor supported on the non-precious metal is then subjected to high-temperature heat treatment under a protective gas environment. The anion exchange resin forms a nitrogen-doped porous carbon support, on which the non-precious metal is uniformly distributed, ultimately forming a catalyst with non-precious metals as the active component and nitrogen-doped porous carbon as the support. This application does not require the direct addition of a carbon support; instead, a porous carbon-nitrogen support is formed while controlling the content and distribution of the active component. The preparation process is simple, low-cost, and can be mass-produced.
Smart Images

Figure CN116742013B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fuel cell catalyst technology, specifically to a non-precious metal fuel cell catalyst, its preparation method, and its application. Background Technology
[0002] Currently, Pt / C catalysts are commonly used in fuel cells, but the use of precious metals in these catalysts leads to high costs. Therefore, research in recent years has gradually shifted towards non-precious metal fuel cell catalysts. Significant progress has been made in the research of carbon-based non-precious metal catalysts in recent years, mainly including carbon-based transition metal sulfides, carbides, nitrides, carbonitrides, oxides, and nitrogen oxides. To date, the preparation of these non-precious metal catalysts has primarily focused on methods with complex processes and demanding preparation conditions, such as template methods, high-temperature calcination methods, chemical vapor deposition methods, and hydrothermal synthesis methods. Due to the complexity of the preparation processes and the large number of dependent variables, the reaction conditions are difficult to control, thus affecting the catalytic activity and stability of the prepared non-precious metal catalysts.
[0003] Therefore, it is of great significance to study a non-precious metal catalyst that has a simple preparation process, controllable reaction conditions, and is suitable for industrial production. Summary of the Invention
[0004] To address the aforementioned shortcomings of existing technologies, the present invention aims to provide a non-precious metal fuel cell catalyst, its preparation method, and its application, thereby solving the problems of complex preparation processes, difficult-to-control reaction conditions, and unsuitability for industrial production in existing non-precious metal catalysts for fuel cells.
[0005] The technical solution of this invention to solve the above-mentioned technical problems is as follows: A method for preparing a non-precious metal fuel cell catalyst is provided, comprising:
[0006] (1) Dissolve the anion exchange resin in water to form an anion exchange resin solution;
[0007] (2) Add a non-precious metal precursor to the anion exchange resin solution to carry out the adsorption reaction. After the adsorption is completed, the solution is dried by centrifugation to obtain the dried product.
[0008] (3) The dried material is heat-treated at 700-1000℃ for 1-4 hours under a protective gas atmosphere, and then pickled and dried to obtain the product.
[0009] The beneficial effects of this invention are as follows: Non-precious metals are adsorbed onto the surface and / or interior of anion exchange resin. After adsorption is complete, the substrate is centrifuged and dried to form a precursor supported on the non-precious metal. This adsorption process allows for control of the adsorption amount of non-precious metals, thereby controlling the loading of active components in the catalyst, while also ensuring uniform distribution of the non-precious metals on the support. The precursor supported on the non-precious metal is then subjected to high-temperature heat treatment under a protective gas environment. The anion exchange resin forms a nitrogen-doped porous carbon support, on which the non-precious metal is uniformly distributed, ultimately forming a catalyst with non-precious metals as the active component and nitrogen-doped porous carbon as the support. This application does not require the direct addition of a carbon support; instead, a porous carbon-nitrogen support is formed while controlling the content and distribution of the active component. The preparation process is simple, low-cost, and can be mass-produced.
[0010] After heat treatment, the heat-treated product is acid-washed to remove acid-soluble impurities, which helps to expose more active sites of the active ingredients and thus improve catalytic efficiency.
[0011] Based on the above technical solution, the present invention can be further improved as follows:
[0012] Furthermore, it also includes a pretreatment process for the anion exchange resin, specifically: grinding and pulverizing the anion exchange resin before use, preferably grinding the anion exchange resin to 30-60 mesh, preferably 60 mesh, the portion larger than 60 mesh is the pretreated anion exchange resin, and then using it in the subsequent adsorption process.
[0013] The beneficial effects of adopting the above-mentioned further technical solutions are as follows: The anion exchange resin used in this invention is a common commercial anion exchange resin. Commercial anion exchange resins can be used directly or after being ground and pulverized. The grinding mesh is 30-60 mesh, which can better adsorb non-precious metals, allowing them to be adsorbed onto the surface and interior of the resin, thereby increasing the content of non-precious metals and improving the catalytic effect of the catalyst.
[0014] Furthermore, the anion exchange resin is dissolved in water to form an anion exchange resin solution with a concentration of 0.05-0.35 g / mL; the weight ratio of the anion exchange resin to the non-precious metal salt is 1:5-3:1.
[0015] The beneficial effects of adopting the above-mentioned further technical solution are as follows: the exchange between the anion exchange resin and metal ions occurs on the surface and inside the resin particles. Since the metal cations are uniformly dispersed in water, and the resin has a strong adsorption effect on the metal cations, the metal cations can be uniformly anchored on the resin surface. When the concentration of the anion exchange resin solution is 0.05-0.35 g / mL, and the weight ratio of the anion exchange resin to water is 1:5-3:1, it is beneficial for the adsorption of metal ions by the anion exchange resin. The amount of anion exchange resin and metal salt used is determined based on the adsorption capacity of the anion exchange resin, and the amount of metal is calculated based on the amount of adsorbed charge.
[0016] Further, in step (2), the adsorption temperature is room temperature - 80°C and the adsorption time is 3-12h; preferably, the adsorption temperature is room temperature and the adsorption time is 4h.
[0017] The beneficial effects of adopting the above-mentioned further technical solution are as follows: water temperature can affect the ion exchange rate. When the adsorption temperature is between room temperature and 80°C, it can promote the ion exchange rate and enable metal ions to be rapidly loaded on the resin. The effect is best when the temperature is room temperature and the adsorption time is 4 hours.
[0018] Furthermore, the non-precious metal is at least one of Fe, Mo, W, Co, Ni, and Mn.
[0019] The aforementioned non-precious metal precursors are often added in the form of salts. Iron is added in the form of sodium ferrocyanide, potassium ferrocyanide, and potassium ferrocyanide; molybdenum is added in the form of ammonium molybdate, sodium molybdate, potassium molybdate, and zinc molybdate; tungsten is added in the form of sodium tungstate, ammonium tungstate, and potassium tungstate; cobalt is added in the form of sodium cobalt cyanide and potassium cobalt cyanide; nickel is added in the form of potassium nickel cyanide and potassium hexacyanide nickelate; tin is added in the form of sodium stannate, potassium stannate, and zinc stannate; and manganese is added in the form of potassium manganate, etc.
[0020] Furthermore, the protective gas in step (3) is nitrogen.
[0021] Furthermore, in step (3), the heat treatment temperature is 900℃ and the heat treatment time is 2h.
[0022] The beneficial effects of adopting the above-mentioned further technical solution are as follows: under the heat treatment temperature and time conditions, the anion exchange resin can form a nitrogen-doped porous carbon support structure without the need to add an additional carbon support. At the same time, during the high-temperature heat treatment, non-precious metals can be well loaded on the support, and the loading amount is controllable, resulting in a catalyst with a large electrochemical area and excellent catalytic activity.
[0023] Furthermore, the acid used in the pickling process in step (3) is hydrochloric acid or nitric acid, with a concentration of 0.5-2 mol / L, respectively; preferably, the concentration is 1 mol / L. Other acids can also be used for pickling, the purpose of which is to remove impurities that can dissolve the acid.
[0024] Furthermore, in step (3), the pickling temperature is 60-80℃ and the pickling time is 2-10h; preferably, the pickling temperature is 70℃ and the pickling time is 8h.
[0025] The beneficial effect of the above-mentioned further technical solution is that pickling with hydrochloric acid or nitric acid of a specific concentration at the above temperature and time can effectively remove impurities.
[0026] The catalysts prepared by the above method can be MoC / NC, WC / NC, Fe-NC, Co-NC, Ni-NC, or Mn-NC. These catalysts can be prepared by directly loading non-precious metals as active components onto nitrogen-doped porous carbon supports obtained after high-temperature heat treatment (such as Fe-NC, Co-NC, Ni-NC, and Mn-NC), or by loading such substances as active components again onto nitrogen-doped porous carbon supports obtained after high-temperature heat treatment (such as MoC / NC and WC / NC).
[0027] The catalyst prepared by the method of this invention has a metal content of 1-10 wt% and a specific surface area greater than 200 m². 2 / g, with a size range of 30nm to 1000nm, and uniform elemental distribution, exhibiting good electrocatalytic effect.
[0028] The above-mentioned catalysts can be used as non-platinum cathode oxygen reduction catalysts in fuel cells, or as catalyst supports.
[0029] Materials that can be used as non-platinum cathode oxygen reduction catalysts in fuel cells include Fe-NC, Co-NC, Ni-NC, and Mn-NC; materials that can be used as catalyst supports include MoC / NC, WC / NC, Fe-NC, Co-NC, Ni-NC, and Mn-NC. Attached Figure Description
[0030] Figure 1 This is the XRD pattern of the catalyst Fe-NC.
[0031] Figure 2 This is the XRD pattern of the catalyst Co-NC.
[0032] Figure 3 This is the XRD pattern of the catalyst Mo-NC.
[0033] Figure 4 The image shows the XRD pattern of the catalyst W-NC.
[0034] Figure 5 This is the XRD pattern of the Ni-NC catalyst.
[0035] Figure 6 The image shows the XRD pattern of the catalyst Mn-NC.
[0036] Figure 7 This is the LSV curve of the catalyst Fe-NC.
[0037] Figure 8 This is the LSV curve of the Co-NC catalyst.
[0038] Figure 9 This is the LSV curve of the Ni-NC catalyst.
[0039] Figure 10 This is the LSV curve of the catalyst Mo-NC.
[0040] Figure 11 This is the LSV curve of the catalyst W-NC.
[0041] Figure 12 This is the LSV curve of the catalyst Mn-NC. Detailed Implementation
[0042] In existing technologies, fuel cell catalysts are prepared by directly adding a carbon support and then loading the active catalyst components onto the carbon support to form the final fuel cell catalyst. Common commercial fuel cell catalysts have very low yields and high costs, making large-scale production impossible. Large-scale production requires specialized manufacturing processes, further increasing costs. Furthermore, the synthesis process of common fuel cell catalysts is complex, with uneven dispersion of metal precursors, making it difficult to effectively control product particle size during subsequent catalyst preparation, resulting in significant agglomeration.
[0043] To address the aforementioned issues, this invention provides a low-cost, large-scale method for producing non-precious metal fuel cell catalysts. The method involves adsorbing non-precious metal salts onto anion exchange resin. After adsorption, the adsorption process is followed by centrifugal drying and then high-temperature heat treatment under a protective gas atmosphere. The heat treatment temperature is 700-1000℃, and the treatment time is 1-4 hours, ultimately yielding the non-precious metal fuel cell catalyst. This catalyst comprises a nitrogen-doped porous carbon support with a size range of 30-1000 nm and a non-precious metal content of 1-10 wt%. The catalyst has a specific surface area greater than 200 m². 2 / g.
[0044] This invention utilizes the adsorption of metals by anion exchange resins, adsorbing metal ions into the resin's functional groups. The adsorption process allows for control over the amount of metal adsorbed by the resin. The amounts of anion exchange resin and metal salt are determined based on the anion exchange resin's adsorption capacity, and the amount of metal is calculated based on the adsorption charge. The metal-loaded resin is cleaned, dried, and ground to obtain dry, metal-loaded resin particles. These particles are then directly heat-treated in a protective gas atmosphere. During heat treatment, the resin forms a nitrogen-doped carbon support, onto which the metal is uniformly distributed. The resulting catalyst is less prone to aggregation, effectively maximizing its catalytic performance. This method eliminates the need for a separate carbon support; instead, the adsorption process simultaneously controls the content and distribution of the active components in the catalyst, forming a carbon support. More importantly, this preparation process is low-cost, simple to operate, and suitable for large-scale industrial production.
[0045] The anion exchange resin used in the preparation process of this invention is a macroporous anion exchange resin with tertiary amine groups [-N(CH3)2]. This type of resin is a commonly used commercial type. Any anion exchange resin that can achieve the above-mentioned technical concept of this application is acceptable. In the embodiments of this invention, resin D301 is preferably used as an example for explanation.
[0046] The examples given below are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified, conditions in the examples are performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0047] Example 1: Catalyst Fe-NC
[0048] A catalyst, Fe-NC, is prepared by adsorbing K3Fe(CN)6 onto an anion exchange resin. The specific preparation process includes the following steps:
[0049] (1) Take resin D301, grind it, and pass it through a 60-mesh sieve;
[0050] (2) Take 1g of the ground resin D301 and add it to ultrapure water to form a solution of 0.1g / mL. Then add 1.263g of K3Fe(CN)6 to the solution, stir and mix evenly, and then centrifuge and dry after adsorption at room temperature for 4h.
[0051] (3) The product obtained in step (2) is subjected to heat treatment in a N2 environment at a temperature of 900℃ for 2 hours.
[0052] (4) The heat-treated material was acid-washed with 1M hydrochloric acid solution at 70°C for 8 hours, then filtered, washed, dried, and ground to obtain the final product.
[0053] Example 2: Catalyst Fe-NC
[0054] The difference between Example 2 and Example 1 is that the heat treatment temperature in step (3) is 1000℃ and the heat treatment time is 1h.
[0055] Example 3: Catalyst Fe-NC
[0056] The difference between Example 3 and Example 1 is that the heat treatment temperature in step (3) is 700℃ and the heat treatment time is 3h.
[0057] The XRD pattern of the Fe-NC catalyst prepared above, taking Example 1 as an example, is shown in the figure. Figure 1 .Depend on Figure 1 It can be seen that Fe-NC was successfully synthesized.
[0058] The LSV curve of the catalyst Fe-NC is shown in the figure. Figure 7 .Depend on Figure 7 It can be seen that the half-slope potential of Fe-NC is 0.850V.
[0059] Example 4: Catalyst Co-NC
[0060] A catalyst, Co-NC, is prepared by adsorbing K3[Co(CN)6] onto an anion exchange resin. The specific preparation process includes the following steps:
[0061] (1) Take resin D301, grind it, and pass it through a 60-mesh sieve;
[0062] (2) Take 1g of the ground resin D301 and add it to ultrapure water to form a solution of 0.1g / mL. Then add 1.27g of K3[Co(CN)6] to the solution, stir and mix evenly, and then centrifuge and dry after adsorption at room temperature for 4h.
[0063] (3) The product obtained in step (2) is subjected to heat treatment in a N2 environment at a temperature of 900℃ for 2 hours.
[0064] (4) The heat-treated material was acid-washed with 1M hydrochloric acid solution at 70°C for 8 hours, then filtered, washed, dried, and ground to obtain the final product.
[0065] Example 5: Catalyst Co-NC
[0066] The difference between Example 5 and Example 4 is that the heat treatment temperature in step (3) is 1000℃ and the heat treatment time is 1h.
[0067] Example 6: Catalyst Co-NC
[0068] The difference between Example 6 and Example 4 is that the heat treatment temperature in step (3) is 700°C and the heat treatment time is 3h.
[0069] The XRD pattern of the Co-NC catalyst prepared above, taking Example 4 as an example, is shown in the figure. Figure 2 .Depend on Figure 2 It can be seen that Co-NC was successfully synthesized.
[0070] The LSV curve of the Co-NC catalyst is shown in the figure. Figure 8 .Depend on Figure 8 It can be seen that the half-slope potential of Co-NC is 0.851V.
[0071] Example 7: Catalyst Mo-NC
[0072] A catalyst, Mo-NC, is prepared by adsorbing (NH4)2MoO4 onto an anion exchange resin. The specific preparation process includes the following steps:
[0073] (1) Take resin D301, grind it, and pass it through a 60-mesh sieve;
[0074] (2) Take 1g of the ground resin D301 and add it to ultrapure water to form a solution of 0.1g / mL. Then add 0.751g of (NH4)2MoO4 to the solution, stir and mix evenly, and then centrifuge and dry after adsorption at room temperature for 4h.
[0075] (3) The product obtained in step (2) is subjected to heat treatment in a N2 environment at a temperature of 900℃ for 2 hours.
[0076] (4) The heat-treated material was acid-washed with 1M hydrochloric acid solution at 70°C for 8 hours, then filtered, washed, dried, and ground to obtain the final product.
[0077] Example 8: Catalyst Mo-NC
[0078] The difference between Example 8 and Example 7 is that the heat treatment temperature in step (3) is 1000℃ and the heat treatment time is 1h.
[0079] Example 9: Catalyst Mo-NC
[0080] The difference between Example 9 and Example 7 is that the heat treatment temperature in step (3) is 700°C and the heat treatment time is 3 hours.
[0081] The XRD pattern of the catalyst Mo-NC prepared above, taking Example 7 as an example, is shown in the figure. Figure 3 .Depend on Figure 3 It can be seen that Mo-NC was successfully synthesized.
[0082] The LSV curve of the catalyst Mo-NC is shown in the figure. Figure 10 .Depend on Figure 10 It can be seen that the half-slope potential of Mo-NC is 0.841V.
[0083] Example 10: Catalyst W-NC
[0084] A catalyst, W-NC, is prepared by adsorbing Na2WO4 onto an anion exchange resin. The specific preparation process includes the following steps:
[0085] (1) Take resin D301, grind it, and pass it through a 60-mesh sieve;
[0086] (2) Take 1g of the ground resin D301 and add it to ultrapure water to form a solution of 0.1g / mL. Then add 1.127g of Na2WO4 to the solution, stir and mix evenly, and then centrifuge and dry after adsorption at room temperature for 4h.
[0087] (3) The product obtained in step (2) is subjected to heat treatment in a N2 environment at a temperature of 900℃ for 2 hours.
[0088] (4) The heat-treated material was acid-washed with 1M hydrochloric acid solution at 70°C for 8 hours, then filtered, washed, dried, and ground to obtain the final product.
[0089] Example 11: Catalyst W-NC
[0090] The difference between Example 11 and Example 10 is that the heat treatment temperature in step (3) is 1000℃ and the heat treatment time is 1h.
[0091] Example 12: Catalyst W-NC
[0092] The difference between Example 12 and Example 10 is that the heat treatment temperature in step (3) is 700°C and the heat treatment time is 3 hours.
[0093] The XRD pattern of the catalyst W-NC prepared above, taking Example 10 as an example, is shown in the figure. Figure 4 .Depend on Figure 4 It can be seen that W-NC was successfully synthesized.
[0094] The LSV curve of catalyst W-NC is shown in the figure. Figure 11 .Depend on Figure 11 It can be seen that the half-slope potential of W-NC is 0.885V.
[0095] Example 13: Catalyst Ni-NC
[0096] A catalyst, Ni-NC, is prepared by adsorbing K2Ni(CN)4 onto anion exchange resin. The specific preparation process includes the following steps:
[0097] (1) Take resin D301, grind it, and pass it through a 60-mesh sieve;
[0098] (2) Take 1g of the ground resin D301 and add it to ultrapure water to form a solution of 0.1g / mL. Then add 0.993g of K2Ni(CN)4 to the solution, stir and mix evenly, and then centrifuge and dry after adsorption at room temperature for 4h.
[0099] (3) The product obtained in step (2) is subjected to heat treatment in a N2 environment at a temperature of 900℃ for 2 hours.
[0100] (4) The heat-treated material was acid-washed with 1M hydrochloric acid solution at 70°C for 8 hours, then filtered, washed, dried, and ground to obtain the final product.
[0101] Example 14: Catalyst Ni-NC
[0102] The difference between Example 14 and Example 13 is that the heat treatment temperature in step (3) is 1000℃ and the heat treatment time is 1h.
[0103] Example 15: Catalyst Ni-NC
[0104] The difference between Example 15 and Example 13 is that the heat treatment temperature in step (3) is 700°C and the heat treatment time is 3 hours.
[0105] The XRD pattern of the Ni-NC catalyst prepared above, taking Example 13 as an example, is shown in the figure. Figure 5 .Depend on Figure 5 It can be seen that Ni-NC was successfully synthesized.
[0106] The LSV curve of the Ni-NC catalyst is shown in the figure. Figure 9 .Depend on Figure 9 It can be seen that the half-slope potential of Ni-NC is 0.899V.
[0107] Example 16: Catalyst Mn-NC
[0108] A catalyst, Mn-NC, is prepared by adsorbing KMnO4 onto an anion exchange resin. The specific preparation process includes the following steps:
[0109] (1) Take resin D301, grind it, and pass it through a 60-mesh sieve;
[0110] (2) Take 1g of the ground resin D301 and add it to ultrapure water to form a solution of 0.1g / mL. Then add 0.6062g of KMnO4 to the solution, stir and mix evenly, and then centrifuge and dry after adsorption at room temperature for 4h.
[0111] (3) The product obtained in step (2) is subjected to heat treatment in a N2 environment at a temperature of 900℃ for 2 hours.
[0112] (4) The heat-treated material was acid-washed with 1M hydrochloric acid solution at 70°C for 8 hours, then filtered, washed, dried, and ground to obtain the final product.
[0113] Example 17: Catalyst Mn-NC
[0114] The difference between Example 17 and Example 16 is that the heat treatment temperature in step (3) is 1000℃ and the heat treatment time is 1h.
[0115] Example 18: Catalyst Mn-NC
[0116] The difference between Example 18 and Example 16 is that the heat treatment temperature in step (3) is 700°C and the heat treatment time is 3 hours.
[0117] The XRD pattern of the Mn-NC catalyst prepared above, taking Example 16 as an example, is shown in the figure. Figure 6 .Depend on Figure 6 It can be seen that Mn-NC was successfully synthesized.
[0118] The LSV curve of the catalyst Mn-NC is shown in the figure. Figure 12 .Depend on Figure 12 It can be seen that the half-slope potential of Mn-NC is 0.904V.
[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a non-precious metal fuel cell catalyst, characterized in that, Includes the following steps: (1) Dissolve the anion exchange resin in water to form an anion exchange resin solution; (2) Add a non-precious metal precursor to the anion exchange resin solution to carry out the adsorption reaction. After the adsorption is completed, centrifuge and dry to obtain the dried product; the non-precious metal is at least one of Fe, Mo, W, Co, Ni and Mn. (3) The dried material is heat-treated at 700-1000℃ for 1-4 hours under a protective gas atmosphere, and then acid-washed and dried to obtain the non-precious metal fuel cell catalysts. The obtained non-precious metal fuel cell catalysts are MoC / NC, WC / NC, Fe-NC, Co-NC, Ni-NC and Mn-NC.
2. The method for preparing the non-precious metal fuel cell catalyst according to claim 1, characterized in that, Anion exchange resin is dissolved in water to form an anion exchange resin solution with a concentration of 0.05-0.35 g / mL.
3. The method for preparing a non-precious metal fuel cell catalyst according to claim 1 or 2, characterized in that, The weight ratio of anion exchange resin to non-precious metal precursor is 1:5-3:
1.
4. The method for preparing a non-precious metal fuel cell catalyst according to claim 1, characterized in that, In step (2), the adsorption temperature is room temperature - 80℃ and the adsorption time is 3-12h.
5. The method for preparing a non-precious metal fuel cell catalyst according to claim 1, characterized in that, In step (3), the heat treatment temperature is 900℃ and the heat treatment time is 2h.
6. The method for preparing a non-precious metal fuel cell catalyst according to claim 1, characterized in that, In step (3), the acid used in the pickling process is hydrochloric acid or nitric acid, with a concentration of 0.5-2 mol / L, respectively; the pickling temperature is 60-80℃, and the pickling time is 2-10h.
7. A non-precious metal fuel cell catalyst prepared by the preparation method according to any one of claims 1-6.
8. The application of the non-precious metal fuel cell catalyst according to claim 7 in the use of a non-platinum cathode oxygen reduction catalyst in a fuel cell or as a catalyst support.
9. A fuel cell, characterized in that, Including the non-precious metal fuel cell catalyst as described in claim 7.
Citation Information
Patent Citations
Preparation method of carbonized Pd (palladium)-carrying hollow anion exchange resin microsphere H2O2 (hydrogen peroxide) electroreduction catalyst
CN104084196A
Direct grown carbon nanotube-based non-noble metal fuel cell catalyst and preparation method thereof
CN113054209A